"It's very hard to change yourself": an exploration of overactivity in people with chronic pain using interpretative phenomenological analysis. Issue 7 (July 2015) - Andrews, Nicole Emma; Strong, Jenny; Meredith, Pamela Joy; Gordon, Kellie; Bagraith, Karl Singh
Abstract : Abstract: Overactivity (activity engagement that significantly exacerbates pain) is a common term in the chronic pain literature. Overactivity is accepted clinically as a behaviour that adversely affects an individual's daily functioning and is the target of one of the most widely endorsed pain management strategies among health professionals (ie, activity pacing). Little research, however, has investigated links between overactivity behaviour and indicators of patient functioning, and activity pacing has not been evaluated as a stand-alone treatment specifically for individuals with chronic pain who are habitually overactive. Two studies, using qualitative research designs and interpretative phenomenological analyses, were conducted to provide insight into (1) why certain individuals develop habitual overactivity patterns in response to pain, (2) the impact of overactivity on daily functioning, and (3) the value of activity pacing as a treatment strategy for this population. Findings suggest that overactivity behaviour is complex, influenced by multiple factors, and negatively impacts on multiple quality-of-life domains. Some participants who were followed up 3 to 6 months after a pain management program were able to learn pacing strategies and enact behaviour change with health professional support; however, the majority reported difficulties changing their behaviour after treatment. It is suggested that provision of pacing education, alone, to chronic pain patients who engage in overactivity behaviour may not be effective in eliciting behavioural change. Key factors that participants believed to contribute to the development and maintenance of their overactive behaviour in this study should be considered in future clinical approaches and empirical investigations. Abstract : Findings from 2 qualitative studies suggest that overactivity behaviour is influenced by multiple factors, negatively impacts on multiple quality-of-life domains, and is difficult to change.